ANALISIS HUKUM BATASAN USIA PERKAWINAN DALAM UNDANG-UNDANG NO. 1 TAHUN 1974 TENTANG PERKAWINAN - Yusmad, Muammar Arafat (Al AHKAM: Jurnal Kajian Ilmu Hukum dan Syariah, 2015)
Marriage is a physically and mentally bond between a man and woman to be husbandand wife to form a happy and eternal family based on the Almighty God. Marriage Law No.1/1974 regulates about marriage age limit. Someone who wanted to marry must reach thecertain age allowed by marriage law. The restriction age for marriage is 19 years old for menand 16 years old for women and also 21 years old for men and women without an obligation toget permission from their parents, is one of the conditions of marriage, but it is not legalrequirement for validity of marriage. The purpose of limitation age for marriage is to care thephysical and mentality health of the couple and also for their children later. This research noted:The violation of the restriction age of marriage is still occurs and it happened due of factorssuch as the occurrence of premarital sex, ignorance of the rules, kinship and other factors.